Curriculum of Intensive Arabic Lessons For The Language Center at The University of Darussalam Gontor - Bobi Ghufron (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Learning Arabic in the world was an importance issue of countries. Therefore, the University of Darussalam Gontor has established a presence in its future vision, which is the formation of the university as a center for the teaching of the language of the Qur'an. Therefore, the University of Darussalam established the Language Center, an Arabic language learning center, and intensive training courses using intensive Arabic language textbooks. It is interesting to note that the center of the language used the book of intensive language lessons and did not use books to teach the other Arabic language. As a result, the researcher wanted to search for the method of intensive Arabic language textbooks. This research is an attempt by the researcher to understand the approach of the book of intensive Arabic language courses in view of the standard of organizing the book, advantages, and deficiency.